Being Soviet and Lithuanian: song festivals as emotional events to induce a hybrid identity. Issue 2 (3rd April 2023) - Putinaitė, Nerija
ABSTRACT: The article analyzes a highly popular phenomenon of the Soviet Lithuanian national culture: the song and dance festivals, regularly organized since 1946. The phenomenon was prevalent in the mass culture until the end of the Soviet era. Following occupation by the USSR in 1940, in order to build a bridge between Soviet and national identity, the Soviet Lithuanian administration promoted song festivals as emotional events to generate a hybrid synthesis of the Soviet ideas and the national elements. Based on both the national tradition and Soviet cultural policies, these events helped blend the national and the Soviet experiences.